Embolis cutis medicamentosa, a rare preventable iatrogenic complication - Manjunath Kavya; Muddanahalli Rajegowda Harish; Kalegowda Deepadarshan; Basavapura Madegowda Shashikumar (Our Dermatology Online, 2015)
Embolis cutis medicamentosa is an uncommon iatrogenic complication characterised by variable degree of skin and tissue necrosis, likely to follow intramuscular injection. Intense pain and purplish discoloration of overlying skin, with or without reticulate pattern subsequently followed by tissue necrosis and scarring is highly specific for this syndrome. It has also been reported following intravenous, intra-articular and subcutaneous injections. Herein we are reporting two cases of this rare preventable entity.